Analysis of Justice Perspective on the Application of Criminal Sanctions in Domestic Violence Cases (Case Study of Verdict No. 622/PID.SUS/2019/PN JKT.UTR) - Qamala, Nurul; Sudarto, Sudarto (Neolectura, 2025)
Domestic violence (DV) is a crime that harms victims physically, psychologically, and socially, violating human rights as regulated in Law No. 23 of 2004 on the Elimination of Domestic Violence. This study analyzes the application of criminal sanctions in Verdict No. 622/Pid.Sus/2019/PN JKT.UTR, where the defendant was sentenced to three years in prison for physically abusing his mother. The study examines the case from a justice perspective using the Theory of Punishment, the Theory of Legal Effectiveness, and the Theory of Justice. Findings indicate that the imposed sanctions were primarily retributive, while preventive and restorative aspects were inadequately applied. The main barrier to achieving substantive justice in this case is the absence of mandatory rehabilitation for perpetrators and the lack of recovery mechanisms for victims. Additionally, the limited gender-sensitive training for law enforcement officials and restricted access to rehabilitation facilities exacerbates the issue. This study recommends revising Law No. 23 of 2004 to mandate rehabilitation for perpetrators, strengthening collaboration between courts and social institutions to support victim recovery, and enhancing legal education for society to prevent domestic violence.